Does the Type Matter? Verification of Different Tea Types' Potential in the Synthesis of SeNPs - Aleksandra Sentkowska; Krystyna Pyrzynska (MDPI AG, 2022)
Selenium nanoparticles (SeNPs) are gaining popularity due to their potential biomedical applications. This work describes their green synthesis using various types of tea. Black, green, red and white tea infusions were tested for the content of polyphenolic compounds and antioxidant properties and then used in the synthesis of SeNPs. In each of the syntheses, nanoparticles with dimensions ranging from 3.9 to 12.5 nm, differing in shape and properties, were obtained. All of them were characterized by a very high ability to neutralize hydroxyl radicals, which was about three-times higher than for the tea infusions from which they were obtained. The main inconvenience in obtaining SeNPs was the difficulties with their purification, which should be a further stage in the described research.